Assessing quality of life of idiopathic pulmonary fibrosis patients: the INSTAGE study - Suarez-Cuartin, Guillermo (Breathe (Sheff), 2019)
The addition of sildenafil to nintedanib treatment does not improve outcomes to a greater extent than monotherapy with nintedanib, and it is not recommended for IPF subjects  http://ow.ly/Gaq530o9kEg